1993
DOI: 10.1007/bf02545314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant population densities and application of growth retardants on cottonseed yield and quality

Abstract: In field trials at Giza in 1986-1987, cotton cv. Giza 75 was sown at 166,000, 222,000 and 333,000 plants/ha and given foliar applications of 0, 250, 500 and 750 ppm Cycocel {chlormequat) or Alar (daminozide}. As plant density increased, there was a decrease in cottonseed yield]ha, seed index, seed protein content, oil and protein yields/ha, oil refractive index, iodine value, unsaponifiable matter and unsaturated fatty acids {myristoleic, oleic and linoleic). In contrast, as plant density increased, there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
22
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 8 publications
15
22
0
Order By: Relevance
“…Application of all PGR significantly increased seed index as compared to untreated control; Pix gave the highest seed index, followed by Cycocel [35]. These agree with previous works of Sawan et al [52], by applying Cycocel and Alar; Carvalho et al [54] by applying Pix and Cycocel; Abdel-Al [50], by applying Pix. Zinc significantly increased seed index compared with the untreated control [35].…”
Section: Analyzed Data For Measurementssupporting
confidence: 89%
See 4 more Smart Citations
“…Application of all PGR significantly increased seed index as compared to untreated control; Pix gave the highest seed index, followed by Cycocel [35]. These agree with previous works of Sawan et al [52], by applying Cycocel and Alar; Carvalho et al [54] by applying Pix and Cycocel; Abdel-Al [50], by applying Pix. Zinc significantly increased seed index compared with the untreated control [35].…”
Section: Analyzed Data For Measurementssupporting
confidence: 89%
“…Similar results were obtained by Gebaly and El-Gabiery [14]. Sawan et al [52] observed that application of Cycocel and Alar (250 -750 ppm, 105 days after planting) increased oil yield ha −1 . Application of Zn resulted in an insignificant increase in seed oil content over that of the control.…”
Section: Analyzed Data For Measurementssupporting
confidence: 86%
See 3 more Smart Citations